»Za otroka« - Šorn, Mojca (Prispevki za novejšo zgodovino, 2024)
After incorporating youth welfare in the framework of public social welfare in 1923, the Ljubljana municipality included in its remit the organisation of holiday colonies for sick children from socially disadvantaged families. The recommendations and precepts of the relevant theory were diligently translated into practice (even during the financially unstable times of the economic crisis and its consequences). Although it did not manage to obtain all the desired or planned resort sites, the children’s colonies became a regular feature of the interwar period. Year after year, the Ljubljana municipality provided for an increasing number of girls and boys, and it should be underlined that they did not only receive medical but also social and educational care.
Keywords: 1918-1941; colonies; kolonije; Ljubljana; mladinsko skrbstvo; youth welfare